The Effect of Work Envy on Employees' Deviant Behavior - Ali Nasre Esfahani; parisa heidari (مطالعات مدیریت بهبود و تحول, 2019)
In today's organizations, considering the bureaucracies and the competitive atmosphere that exists, attention to the feelings of people, especially the feeling of jealousy at work is of particular importance. The purpose of this research is to investigate the effect of envy at work on employees' deviant behavior. This research is applied in terms of purpose and is a survey-descriptive in terms of collecting data. The statistical population of Isfahan Steel Technic Co. employees was used by simple random sampling. To analyze the collected data and to conduct the research, PLS 2.0 software was used. The statistical population consisted of 300 executives and experts of Isfahan Steel Technique Co., and 90 people were evaluated using simple random sampling for analysis. PLS 2.0 software was used for conducting the research. The results indicate that jealousy at work and its components have a positive and significant effect on deviant behavior. Since jealousy at work causes deviant behaviors in the organization and cause damage to the organization's core body, attention to employees' feelings, such as jealousy, is important. Therefore, the organization and management, taking into account the system of proper performance evaluation and considering the equal conditions of each person's performance is properly investigated and the results presented to everyone so that if there is any ambiguity to prevent any behavior that could harm the organization in the future. Management can, by organizing the organization's culture, tell employees that everyone has the ability and skills to compete with others instead of jealousy and move in one direction in order for the organization to succeed. Controlling the sense of jealousy at a reasonable level can be in the best interest of the organization so that employees can compete with each other to increase productivity, and if they do not pay attention to the feeling of jealousy, employees may be in violation of their partner's failure and it leads to the organization's failure to compete.